DISTRIBUITION OF CRUSTOSE CORALLINE ALGAE (CORALLINALES, RHODOPHYTA) IN THE ABROLHOS REEFS, BAHIA, BRAZIL - Tâmega,Frederico Tapajós de Souza (2007)
ABSTRACT The crustose coralline algae have an important structural role in coral reef crests, as observed for some Atlantic reefs. In this work the distribution and abundance of crustose coralline algae and their relation to other benthic reef organisms were described for the Abrolhos Archipelago. The quantification of sessile organisms was made by SCUBA diving along replicated transect lines in different habitats and sites. Anovas were performed to test differences on algae abundance among sites and habitats. Coralline crusts did not show significant differences on abundance among sites (Anova, p>0,05), neither other benthic organisms (Anovas, p=0,634 invertebrates, p=0,767 filamentous algae, p=0,581 foliose algae, p=0,070 leathery algae and p=0,616 non calcareous crusts). Invertebrates and filamentous algae were the most abundant organisms on all sites and most habitats, contrasting with the low cover of coralline algae. In sheltered sites and on reef base it was observed a trend for an increase of fleshy foliose algae and leathery algae, contrasting with wave exposed sites. The distribution of coralline growth forms was characterized by a higher abundance of flat in relation to branched thalli. Branched coralline crusts are apparently more abundant within cryptic reef areas, not necessarily because of light limitation, but probably due to less herbivore pressure.